Husband participation in birth preparedness and complication readiness and its predictors among men whose wife was admitted for an obstetric referral at South Gondar zone: A multicenter cross-sectional study - Getaneh Atikilt Yemata; Gojjam Dessibellew; Atsede Alle; Yilkal Tafere; Abirham Wallelign Bayabil; Eyaya Habtie Dagnaw (Heliyon, 2023)
Background: Husbands' participation in maternal health care, as seen by an appropriate birth plan and readiness for complications, reduces maternal death by avoiding delays in recognizing danger signs, reaching a site of care, and seeking aid. As a result, this study aimed to determine the husband's participation in birth preparation and complication readiness, as well as its predictors, among men whose wives were referred to obstetric referral in the South Gondar Zone of North West Ethiopia. Methods: A hospital-based cross-sectional study was conducted among husbands whose wives were admitted with obstetric referrals in the selected hospitals from February to March 2021. A total of 393 individuals were chosen proportionally from the selected hospitals using a systematic random sampling technique. An interviewer-administered structured questionnaire was used to collect data, which was then entered into Epi Data Version 3.1 and exported to Stata version 14 for analysis. To find predictors of the outcome variable, a binary logistic regression model was used. The final model's results were expressed as adjusted odds ratios, 95% confidence intervals, and P-values. Result: The magnitude of husband participation in birth preparedness and complication readiness among obstetric referrals was 282 (71.8%). Planned pregnancy [AOR, 95% CI: 2.78 (1.68–4.62)], discussion with their wife [AOR, 95% CI: 2.85 (1.72–4.71)], and good knowledge of danger signs during pregnancy, delivery, and postpartum [AOR, 95%CI:2.71 (1.67–4.42)] were significantly associated with husband participation as compared to its counterparts. Conclusion and Recommendation: The husband's participation in birth preparedness and complication readiness for obstetric referrals in the South Gondar zone were reasonably good. For good husband participation in birth preparedness and complication readiness, knowledge of danger signs, pregnancy planning status, and discussion with wife about pregnancy were responsible. Healthcare providers should support mothers in discussing the danger signs of pregnancy, birth preparedness, and complication readiness with their husbands during ANC visits.